A new low molecular weight, MnII-containing scavenger of superoxide anion protects cardiac muscle cells from hypoxia/reoxygenation injury. (January 2015) - Nistri, S.; Boccalini, G.; Bencini, A.; Becatti, M.; Valtancoli, B.; Conti, L.; Lucarini, L.; Bani, D.
Abstract: Reperfusion injury after oxygen starvation is a key pathogenic step in ischemic diseases. It mainly consists in oxidative stress, related to mitochondrial derangement and enhanced generation of reactive oxygen species (ROS), mainly superoxide anion (O2 2 ), and peroxynitrite by cells exposed to hypoxia. This in vitro study evaluates whether Mn II (4, 10-dimethyl-1, 4, 7, 10-tetraazacyclododecane-1, 7-diacetate).2H2 O, or Mn II (Me2 DO2A), a new low molecular weight, Mn II -containing O2 scavenger, has a direct protective action on H9c2 rat cardiac muscle cells subjected to hypoxia and reoxygenation. Mn II (Me2 DO2A) (1 and 10 μmol/l) was added to the culture medium at reoxygenation and maintained for 2 h. In parallel experiments, the inactive congener Zn II (Me2 DO2A), in which Zn II replaced the functional Mn II center in the same organic scaffold, was used as negative control. Mn II (Me2 DO2A) (10 μmol/l) significantly increased cardiac muscle cell viability (trypan blue assay), improved mitochondrial activity (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide test, membrane potential Δψ), reduced apoptosis (mitochondrial permeability transition pore opening, caspase-3, terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end labeling assay), decreased intracellular ROS levels (2', 7'-dichlorodihydrofluorescein diacetate and MitoSOX assays), and decreased protein nitroxidation (nitrotyrosine [NT] expression) and DNA oxidation (8-hydroxy-deoxyguanosine levels). Of note, Zn II (Me2 DO2A) had no protective effect. The mechanism of Mn II (Me2 DO2A) relies on concentration-dependent removal of harmful O2 generated at reoxygenation from dysfunctional mitochondria in hypoxia-induced cells, as indicated by the MitoSOX assay. This study suggests that Mn II (Me2 DO2A) is a promising antioxidant drug capable of reducing O2 -mediated cell oxidative stress which occurs at reoxygenation after hypoxia. In perspective, Mn II (Me2 DO2A) might be used to reduce ischemia–reperfusion organ damage in acute vascular diseases, as well as to extend the viability of explanted organs before transplantation.